ZOOM bahaya ZOOM dipakai - Zulhuda, Sonny (2020)
This presentation discusses issues of law, governance and risk management surrounding the use of web conference platform. Among the prevalent issues are security and privacy of data. It focuses on both international and Indonesian legal framework.